Post a New Question

Math

posted by on .

Solve the equation or inequality for
3(2y-4)=9-3(y+1)The answer is 2. How do you work it out to get the answer?



(x+5)(x-3)=9 the answer is -6,4
How do you work it out????

  • Math - ,

    first one:
    3(2y-4)=9-3(y+1)
    6y - 12 = 9 - 3y - 3
    6y + 3y = 6+12
    9y = 18
    y = 2

    2nd:
    (x+5)(x-3)=9
    x^2 - 3x + 5x - 15 = 9
    x^2 + 2x - 24 = 0
    (x+6)(x-4) = 0
    so x+6 = 0 or x-4 = 0
    x = -6 or x = 4

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question